Karl Friedrich Schinkel, uma Teoria da Prática - Teresa de Jesus da Silva Costa Ferreira (2010)
"Knowledge, information, the study of architects and architectural history should move or tend to be assimilated, until lost in the unconscious or the subconscious of each." Karl Friedrich Schinkel (1781-1841), Prussian architect of the early nineteenth century, made compelling projects throughout his career. Schinkel essentially worked for the royal family and his work can be characterized by high quality, research and constant experimentation. "Schinkel evolved from romantic to classical architect, who left his mark on the new city of Berlin, which then became known as the Athens of the River Spree." T his dissertation focuses on the built work of Schinkel in a possible reading of contemporary architecture in the light of his teachings. Thus, the narrative is divided into two major parts. The first is primarily an interpretative reading of some main issues of Schinkel's work, where we emphasize the construction of villas for the royal family, the requalification of Berlin's center and his interest in technology and construction. The second part focuses on the influence of Schinkel in most current contexts: Mies van der Rohe and the Schinkelesque space, Eduardo Souto de Moura interest in the classical tradition and the ornament in the work of Herzog & de Meuron, recovering some of the topics covered in the first part. T hrough some case studies analysis, including the most important of Schinkel's projects, as the Neue Wache (Home Guard) the Altes Museum or the Bauakademie, the approach to the problems of contemporary architecture as well as the production of a critical view is emphasized as a contribution to the instruction of architects. In this sense, Schinkel says, "the work of a true learning should be difficult, but ultimately reduces the formation of a sensibility, that in architecture covers a very broad field."